The validity of computerized visual motor integration assessment using Chinese basic strokes. Issue 8 (17th November 2018) - Li, Cheng-Hsuan; Wu, Huey-Min; Kuo, Bor-Chen; Yang, Yu-Mao; Lin, Chin-Kai; Wang, Wei-Hsiang
ABSTRACT: The purpose of this study is to explore the validity of the assessment tool. The purposive sampling method is applied in this research on a total of 551 preschool children between 4 and 6 years old. Their ages range from 46 to 81 months, with an average age of 63.9 months ( SD = 7.58). The assessment tool used in this research is the "Computerized Visual Motor Integration Assessment Tool Using Chinese Basic Strokes". The multivariate logistic regression analysis was used to automatically determine children's writing classification. The findings suggest that the assessment tool developed has good validity in terms of sensitivity, specificity and the accuracy. This tool is recommended for use in the diagnosis of Chinese visual motor integration issues for preschoolers, so that their potential writing difficulties may be detected early, and the goal of early intervention may be achieved.